THE ESSENCE OF LEGAL RESPONSIBILITY OF SUBJECTS OF INTERNATIONAL LAW - Лобжанідзе, Гіві; Лобжанідзе, Давид (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: to analyze the essence of legal responsibility of subjects of international law. To characterize the different types of complicity of states and other entities in the commission of an international offense, to assess the prevalence of the principle of unavoidable international legal responsibility. Research methods: the use of the dialectical and historical method of cognition allowed to concentrate the accumulated scientific knowledge and reveal the essence of the legal responsibility of the subjects of international law. Results: the international legal responsibility, despite of specific specificity, is one of the serious factors from the point of view of prevention of an offense. Discussion of the problem: many scientists identify the concept of objective and absolute responsibility, but there are among them those who differentiate between them.